Perseverance Practices in Small and Medium Enterprises: An Entrepreneurial Perspective for Business Growth and Internationalization - Orengo Serra, Karen Lizzette (2017)
Through a qualitative case study approach, this study describes the dynamics between perseverance strategies and entrepreneurial traits in SMEs that have been leaders in their markets since their foundation. The selected sample is among the iconic well-known businesses of their respective countries. For this study we reframed the perseverance strategies of Van Gelderen (2012). The enterprise perseverance practices served as a mechanism for strategic entrepreneurial reorientation and constant renewal of the enterprise. These perseverance practices are triggered by the entrepreneurial attitudes of the owners, whose knowledge acquisition and commitment to the market facilitate innovation, creativity, and the identification of networks encouraging business growth and internationalization of the firm.